INFORMATIVENESS AND SPECIFICITY OF SERUM OSTEASE LEVEL IN THE DIAGNOSIS OF OSTEOPENIC SYNDROME IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS - Ilchenko, Svitlana; Makoviichuk, Oleksii; Fialkovska, Anastasiia (Eastern Ukrainian Medical Journal, 2024)
Introduction. Low bone mineral density (BMD) is a common phenomenon in the clinical practice of a pediatric rheumatologist. Children with juvenile idiopathic arthritis (JIA) are at risk of developing osteopenic syndrome (OS) due to both primary and secondary mechanisms. Routine laboratory diagnostic methods for bone disorders, including the determination of calcium, phosphorus, and total alkaline phosphatase (ALP) concentrations in blood serum, have low specificity in children with JIA and often remain within normal ranges for extended periods. The activity of the bone isoenzyme ALP (ostease) and its association with disease progression require further study to improve the diagnosis and prognosis of OS in pediatric patients. The aim of the study was to establish the diagnostic significance of the level of serum ostease in the diagnosis of OS in children with JIA. Materials and methods. A total of 50 children with JIA, aged 5 to 18 years, were examined. Laboratory research methods included determination of the concentration of 25-hydroxyvitamin D (25(OH)D), total ALP, bone isoenzyme of ALP – osteoase (BAP), marker of bone resorption – β-Cross Laps, osteocalcin in blood serum. BMD screening was conducted using the Sunlight Omnisense 9000 ultrasonic densitometer. Statistical analysis of the results was performed using the Statistica v.6.1 software package Results and their discussion. OS was diagnosed in children with JIA in 42.0 % of cases. It was established that children with OS had significantly lower concentrations of osteoase in blood serum. The level of osteoase in children with OS was related to the level of 25(OH)D, osteocalcin, marker of bone resorption – β-Cross Laps, Z-score according to ultrasound densitometry, disease activity and the dose of methotrexate in basic therapy. At the same time, the activity of total ALP in the blood serum of children with JIA did not differ significantly between subgroups. No correlation was found between the level of total ALP and its bone isoenzyme – osteoase, as well as the level of 25(OH)D, disease activity, and Z-score. Based on ROC analysis, an optimal threshold for BAP in diagnosing OS in children with JIA was determined as >83.4 μg/L (sensitivity – 85.7 %, specificity – 93.1 %, diagnostic accuracy – 90.0 %, area under the curve (AUC) – 0.864 (95% CI 0.737–0.944)). Conclusions. Elevated BAP levels in blood serum in children with JIA should be considered an informative and highly specific biomarker for the early diagnosis and prognosis of OS. Total ALP in children with JIA is a non-specific marker, as normal serum activity does not rule out abnormalities in the bone isoenzyme pattern.